2021
DOI: 10.5603/fm.a2020.0022
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery variations revised: origin, course, branches and embryonic development

Abstract: Background: The vertebral artery originates from the subclavian artery and is divided into four segments. The aim of this study is to investigate the anatomical variations in the course and branches of the vertebral artery. Materials and methods: A research was performed via Pubmed database, using the terms; "variations of vertebral artery AND cadaveric study", "variations of vertebral artery AND cadavers" and "anomalies of vertebral artery AND cadavers". Results: A total of 24 articles met the inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 39 publications
(73 reference statements)
3
38
0
1
Order By: Relevance
“…Extradural origins of VA, similar to our ndings, were reported in about 4% of patients through previous studies [20]. PICA termination is widespread in cases of left VA origin from the aortic arch, and the extradural branches of VA should be taken into consideration [13].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Extradural origins of VA, similar to our ndings, were reported in about 4% of patients through previous studies [20]. PICA termination is widespread in cases of left VA origin from the aortic arch, and the extradural branches of VA should be taken into consideration [13].…”
Section: Discussionsupporting
confidence: 88%
“…With advances in interventional radiology and surgical methods in the neck, a thorough knowledge of VA's anatomical variations regarding its origin, course, and branches is crucial to minimize procedurerelated complications [13]. Although colour Doppler ultrasonography has been traditionally considered the primary diagnostic modality in VA variations, CTA and MR angiography more accurately depict these variations and anomalies [14].…”
Section: Discussionmentioning
confidence: 99%
“…An extradural origin PICA from the VA is not rare. The frequency of an extradural origin of the PICA ranges from 0.4% to 20.8% 1 , 4 , 12 , 18 , 19 , 22 - 25 . The extradurally located PICAs are exposed to injury during posterior approaches to the lower brainstem and upper cervical spine.…”
Section: Introductionmentioning
confidence: 99%
“…A normal VA is divided into 4 segments: V1 segment (It originates from the subclavical artery and enters the C6 transverse process), V2 segment (walks through C6-2 transverse process), V3 segment (the segment courses from C2 to the foramen magnum), and V4 segment is coursing from entering the cranium to attending the basilar artery. 9 Wang et al 10 has previously reported anatomical V3 segment variations of VA in patients with atlas occipitalization. The bone deformity of "sandwich" AAD patients was more serious than mere atlas occipitalization, and the combined VA deformities may be more complex, which have not been reported yet.…”
Section: Neurospine Eissn 2586-6591 Pissn 2586-6583mentioning
confidence: 99%